DevelopinDEVELOPING CORPORATE RESILIENCE IN NIGERIAN SMES: THE ROLE OF MANAGEMENT CONSULTANTS IN SOUTHERN NIGERIAg corporate Resilience in Nigerian SMES: The role of Management Consultants in Southern Nigeria - Goodey C. , Chikwe; Nwaji, Charles; Abbey-Kalio, Boma (International Journal For Research In Business, Management And Accounting, 2017)
this paper focused on developing corporate resilience in Nigerian SMEs: the role of management consultants in southern Nigeria. The paper adopted survey approach and the major instrument for data collection was a five point likert scale questionnaire. The data gathered was analyzed with t-test using the 20.0 version of the statistical package for social sciences (SPSS) at 0.05 level of significance. The study covered a population of 512 persons which consists of 112 management consultants and 400 management staff of 60 selected SMEs from Enugu, Imo and Rivers-state. The researchers used the Yaro Yamene’s method to select a sample size of 225 persons. It was concluded in this paper that SMEs should develop resilience drive in their business approaches. The study found that due to dearth of resources and internal capabilities, there is need for SMEs to leverage on the services of management consultants. The p-value shows a 0.001 and 0.002 outputs, which reflects the significant contributions management consultants can make to the development of resilience in SMEs in turbulent times. This paper therefore recommends among others that state governments in southern Nigeria should provide business resilience targeted trainings to managers and owners of SMEs in order to prepare them with relevant and current knowledge that can guide their operations.